Hubungan Perilaku Pemilihan Makanan Sehat dan Konsumsi Sugar-Sweetened Beverage dengan Kejadian Menarche pada Remaja Putri - Ritma Dewanti; Afiska Prima Dewi (Jurnal Sains dan Kesehatan, 2026)
Background: Adolescence is often characterized as a period of puberty. Early menarche is associated with increased mortality and morbidity risks in later life among girls who experience menarche at an early age. Menarche is the first menstrual event in girls, marked by the shedding of the uterine lining and vaginal bleeding. The tendency to consume unhealthy foods, particularly fast food, as well as sugar-sweetened beverages (SSBs), may have adverse effects on health and potentially influence the timing of menarche. Objective: This study aimed to analyze the relationship between healthy food selection, sugar-sweetened beverage consumption, and the incidence of early menarche. Methods: This study employed a cross-sectional design. The sample consisted of 30 female students. Data were analyzed using the Spearman Rank correlation test. Results: The results showed that healthy food selection was significantly associated with the incidence of early menarche (p = 0.005) with a moderate correlation strength (ρ = 0.449). Similarly, sugar-sweetened beverage consumption was significantly associated with the incidence of menarche (p = 0.000) and demonstrated a very strong correlation (ρ = 0.841). Conclusion: There was a significant relationship between healthy food selection and sugar-sweetened beverage consumption with the incidence of menarche. Sugar-sweetened beverage consumption showed a stronger relationship with menarche incidence compared to healthy food selection.